Repositioning speech language pathology practices: engaging with family and community narratives to evolve communication supports for neurodivergent children - Parusnath, Prianka (Department of Health and Rehabilitation Sciences, 2025)
In South Africa and the Majority World, Speech-Language Therapy services are not easy to access. The profession with its medical model roots can be elitest, reductive and ineffective in areas where therapists are a finite resource. The purpose of this study was to engage with families and communities in order to evolve communication supports for neurodivergent children with the focus on community practice, inclusion and belonging. Additionally, story telling was used as the vehicle for learning. These stories were further explored in the context of South Africa with a specific focus on Disability in the Majority World, Inclusion and Belonging, Decolonisation within the framework of current practice and Practice Shifts (currently taking place and on the horizon). In order to do explore these concepts, narrative interviews were conducted with four families and two community members in order to learn about their experiences regarding inclusion and belonging. The families all have children who access alternative communication and the focus of the interviews were to gain insight into their journeys and experiences with Speech Language Therapy, communication and how this impacted their experiences in their community. After analysis of these interviews, the stories were shared at a workshop attended by various professionals (teachers, psychologists, speech therapists etc.) to explore the impact that stories have on therapeutic learning and practice shifts. The analysis occurred in two phases. First a narrative analysis was conducted for each family and community member post interview. Then an analysis of the narratives was conducted which culminated in themes being curated. Graphic Harvesting and Thematic Analysis were used to analyse the workshop discussion. The most significant finding and a common thread in every family narrative was the burden of communication that was placed on them when Speech Therapists practiced in traditional ways (i.e. in therapy rooms behind closed doors). Additionally, exclusion was also prominent theme that arose, firstly just because the child has a disability and then secondly because alternative communication was seen as so different and “other” that it was further isolating. There was a definite call from families for practice shift that supported them more holistically out in their community. The Invisible String is a conceptual framework that proposes the union of decolonised practice concepts with the intersectionality of the families we work with. The image is of a patchwork quilt, families on one side, decolonial practise on the other with Speech-Language Therapists being the guiding hand to the needle of communication. The thread that binds it all is community. It is an offering of reuniting and remaking and bringing humanity and community to the forefront of practice.